Dispositivos de controle e as práticas de ressocialização dentro do cárcere - COSTA, Jemerson Willis Alves da (2023)
The present research has as its theme the practice of resocialization within prison. for discussion on the subject, it is necessary to elucidate some interrelationships that are established between the concepts. Initially, it is necessary to keep in mind that everything that governs the norms of social conduct was and is invented, it is na established social agrément. In this way, notions such as prison and imprisonment and resocialization are invented conceps, created as a technique for controlling the individual. Those who do not obey, and do not conform to the norms, are punished. Taking this into account, the problem of the presente work resides in the way in which prisoners are treated inside the prison, or Rather, on the profile of the prisoner and practices of resocialization practice. Therefore, the research question is: what are the resocialization practices within prison? Therefore, the general objective of the research resides in: understanding the practice of resocialization within prison. To achieve this objective, a qualitative research was carried out. it is concluded that there needs to be a change in the mentality of both Society na the public power in relation to the prisoner so that there is na effective resocialization.